2006
DOI: 10.1007/s11663-006-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of microwave heating of particulate metals

Abstract: Recent studies have shown that metal powder compacts can be heated to high temperatures using microwaves. While microwave heating of ceramics is well understood and modeled, there is still uncertainty about the exact mechanism and mode of microwave heating of particulate metals. The current study describes an approach for modeling the microwave heating of metal powder compacts using an electromagnetic-thermal model. The model predicts the variation in temperature with time during sintering. The effect of powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 18 publications
0
62
0
2
Order By: Relevance
“…[5][6][7][8][9] Magnetic and refractory powder metals appear to respond well to MW radiation compared with other powder metals which often show mild or weak responses. [10][11][12][13] Using the Heisenberg model, Tanaka et al [14] have recently shown that MW radiation can heat magnetic metal oxides to temperatures well above their Curie temperatures while it is essentially ineffective for non-magnetic oxides. Their modeling identified that such fast heating ''is caused by nonresonant response of electron spins in the unfilled 3d shell to the wave magnetic field,'' [14] and the effect ''persists above the Curie temperature T c because each electron spin is able to respond to the alternating magnetic field of MWs even above T c .''…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Magnetic and refractory powder metals appear to respond well to MW radiation compared with other powder metals which often show mild or weak responses. [10][11][12][13] Using the Heisenberg model, Tanaka et al [14] have recently shown that MW radiation can heat magnetic metal oxides to temperatures well above their Curie temperatures while it is essentially ineffective for non-magnetic oxides. Their modeling identified that such fast heating ''is caused by nonresonant response of electron spins in the unfilled 3d shell to the wave magnetic field,'' [14] and the effect ''persists above the Curie temperature T c because each electron spin is able to respond to the alternating magnetic field of MWs even above T c .''…”
Section: Introductionmentioning
confidence: 99%
“…The emitted heat of the plate warms the radiometer, so the prototype is enclosed and cooled with compressed air to maintain the radiometer temperature at 20 • C, avoiding gain drift due to temperature variations. Another problem found in the preliminary experiments was the low thermal emissivity of metals [9]. However, the measured plate is slightly oxidized.…”
Section: Experimental Hostile Scenariomentioning
confidence: 94%
“…Density, specific heat capacity and thermal conductivity of the studied powders are assumed constant with respect to temperature in this study. However, the specific heat capacity of iron powder compact can be made temperature dependent considering the temperature dependent heat capacity function [23,24] expressed as: It is worth mentioning that use of temperature dependent C p as model input will make the high temperature processing of iron powder more effective.…”
Section: Estimation Of Effective Constitutive Propertiesmentioning
confidence: 99%